Spatiotemporal changes in terrestrial water storage in the Beijing-Tianjin Sandstorm Source Region from GRACE satellites - Yingjun Pang; Bo Wu; Yanping Cao; Xiaohong Jia (International Soil and Water Conservation Research, 2020)
The Sandstorm Source Control Project in and around the Beijing-Tianjin region was one of the most important ecological projects in China. Terrestrial water storage (TWS) has important impacts on the ecological construction, agriculture, industry, and resident’s lives. Based on the Gravity Recovery and Climate Experiment (GRACE) data, meteorological and Moderate Resolution Imaging Spectroradiometer (MODIS) data, etc., this paper analyzed spatiotemporal characteristics of TWS, groundwater storage, and precipitation, and explored the influencing factors of regional TWS combined with land use and land cover (LULC), social and economic data. The most important results were as follows: (1) From 2003 to 2016, TWS in the Beijing-Tianjin Sandstorm Source Region showed a decreasing trend with a rate of 3.14 mm yr−1. (2) The TWS decline was caused mainly by groundwater overexploitation, but not precipitation variation. (3) Spatiotemporal variations of TWS were related to LULC. The area with the most serious decrease of TWS was mainly located in the southwestern part of the region, where farmland percentage and population density were greater. (4) Reducing the percent of farmland and tree planting, and adding the shrub and grass planting, could be a viable choice for the Beijing-Tianjin Sandstorm Source Control Project. These results provide a scientific basis for regional water resource and ecological management.